Warna Syara’ Pada Fungsi Bundo Kanduang Di Minangkabau - Suhefri Suhefri; Sindia Ayu (Mathematics Education Study Program, 2025)
Bundo Kanduang is a figure who holds a central role in Minangkabau society, not only in the context of tradition (adat) but also within the framework of Islamic values (syara’). This article discusses how Islamic values (syara’) are implemented in the functions of Bundo Kanduang in Minangkabau. The study employs a qualitative method with a descriptive-analytical approach. Data were collected through literature reviews and interviews with traditional leaders and religious figures in Minangkabau. The findings reveal that Bundo Kanduang's role is closely related to the principle of